Peak characteristics of F2 region over Tucumán: Predictions and measurements - Ezquer, Rodolfo Gerardo (2008)
Ionosonde measurements obtained at Tucuman are used to check the validity of the International Reference Ionosphere model to predict the maximum electron density of F2 region (NmF2) and its height (hmF2) over this station. Data corresponding to different months and solar activity conditions are considered. CCIR and URSI options are used to model calculations. The results show that, generally, the predictions of hmF2 are better than those of NmF2. Disagreements between predicted and measured NmF2 values are observed and the consequence in the vertical total electron content modeling are stressed.